Nderep and Agricultural Philanthropy: Local Zakat Practices in Rural Kalisalak - Dwi Kuswianto; Cinanthya Yuwono; Fatih Atsaris Sujud; Faqih Abdulloh (Program Studi Manajemen Zakat dan Wakaf, 2026)
This study explores nderep, a traditional harvest-sharing practice in Kalisalak Village, Tegal Regency, as a form of agricultural philanthropy rooted in Islamic values and local wisdom. Employing a qualitative ethnographic approach through observation and in-depth interviews, the research finds that nderep embodies distributive justice, mutual cooperation (gotong royong), and social piety, resonating with the essence of zakat al-zur‘. The novelty of this study lies in reframing nderep not merely as agrarian labor tradition but as a community-based Islamic philanthropic mechanism with redistributive functions. Empirical findings indicate diverse harvest-sharing patterns that mitigate inequality between landowners and farm workers while sustaining communal solidarity. Within the theoretical framework of Islamic philanthropy and community-based zakat, the research demonstrates that nderep offers significant potential for hybrid integration into formal agricultural zakat systems, bridging traditional practices with institutionalized mechanisms. The study concludes that recognizing and institutionalizing such indigenous practices can contribute to the development of a more contextual, inclusive, and sustainable zakat model. It recommends strategic collaboration between zakat institutions, religious leaders, and farming communities to optimize agrarian-based philanthropy for rural welfare.